Densely pillared holey-graphene block with high-level nitrogen doping enabling ultra-high volumetric capacity for lithium ion storage. (February 2019) - Zhang, Longhai; Yue, Jingming; Wei, Tong; Liu, Zheng; Zhou, Jiali; Liu, Chaoqun; Jiang, Han; Jiang, Zimu; Fan, Zhuangjun
Abstract: Developing high volumetric capacity and long cycle-life anode materials for high-performance lithium-ion batteries (LIBs) still remains a great challenge. Herein, densely pillared holey-graphene block with high N-doping (P-NHG) has been successfully synthesized through thermal decomposition of (NH4 )6 Mo7 O24 in-between stacked GO sheets. The dense graphene building block processes a high packing density of 2.53 g cm −3, high nitrogen doping (19.2 at%), numerous holes on the graphene sheet, and ∼5 nm Mo2 C nanoparticles as the pillars in-between the graphene sheets, facilitating rapid ion diffusion and storage and ensuring structural stability during Li ion storage. As a result, the P-NHG electrode can deliver high gravimetric capacity of 1221 mAh g −1 and ultrahigh volumetric capacity of 3089 mAh cm −3  at 0.1 A g −1, as well as excellent cyclability (713 mAh g −1 /1803 mAh cm −3 after 300 cycles at 0.5 A g −1 ). The novel design of densely pillared holey-structure materials represents greatly improved properties such as superior cyclability, and high volumetric capacity for LIBs. Graphical abstract: Image 1